Effect of Methylphenidate on the Immune System - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The effects of methylphenidate (MPH) on the immune system was studied in laboratory mice and in 6 healthy boys treated for ADHD with 30-45 mg/day MPH at the Kings County Hospital, Brooklyn, NY.